2018
DOI: 10.3390/jmse6020052
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Propeller-Induced Hull Pressure Fluctuations via a Potential-Based Method: Study of the Effects of Different Wake Alignment Methods and of the Rudder

Abstract: Abstract:In order to predict ship hull pressure fluctuations induced by marine propellers, a combination of several numerical schemes is used. The propeller perturbation flow is solved by the boundary element method (BEM), while the coupling between a BEM solver and a Reynolds-averaged Navier-Stokes (RANS) solver can efficiently predict the effective wake. Based on the BEM solution under the predicted effective wake, the propeller-induced potential on the ship hull can be evaluated. Then, a pressure-BEM solver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This is limited to the vicinity of the propeller's position and might be considered reaching no further upstream than up to 10 times propeller disc diameter (Vladimir Krasilnikov, 2014). The dominant interaction of the propeller's pressure field and the hull is by vibration induction when the tip pressure peaks pass by the aft ship above the propeller and induce noise and vibrations in the hull (Su et al, 2017;SVA Potsdam, 2015). What isn't that obvious is to reckon quantitatively the degree of propeller's influence on squat in very shallow water.…”
Section: Influence Of Propeller On Squatmentioning
confidence: 99%
“…This is limited to the vicinity of the propeller's position and might be considered reaching no further upstream than up to 10 times propeller disc diameter (Vladimir Krasilnikov, 2014). The dominant interaction of the propeller's pressure field and the hull is by vibration induction when the tip pressure peaks pass by the aft ship above the propeller and induce noise and vibrations in the hull (Su et al, 2017;SVA Potsdam, 2015). What isn't that obvious is to reckon quantitatively the degree of propeller's influence on squat in very shallow water.…”
Section: Influence Of Propeller On Squatmentioning
confidence: 99%
“…The unsteady wake alignment scheme was first introduced by Lee (2004) [17] and has been improved by Kim (2017) [13], such that the alignment scheme allows the variation of wake panels in non-periodic inflow conditions. [18] first employed this alignment scheme in calculating the hull pressures, and it was shown that the unsteady wake behaved better when predicting the downstream hull pressures in fully-wetted case. In this article, the alignment algorithm is coupled with the Full Wake Alignment (FWA) scheme by Tian & Kinnas (2012) [19] and [20], which models the trailing vortices as material lines, following the local stream in steady state.…”
Section: The Unsteady Wake Alignment Schemementioning
confidence: 99%
“…It takes five iterations for the BEM/RANS coupling method to produce the converged forces and the effective wake field within 2 h of the wall-clock computing time. To study the effect of the rudder in the predicted propeller-induced hull pressure, a test was made by Su (2017) [18], in which the two cases are tested in the pressure BEM model: one includes only the upper part of the rudder, the other is totally neglecting the rudder geometry. According to the presented results, the difference is negligible except the transducers relatively close to the leading edge of the rudder.…”
Section: Sspa P2772 Propeller In Effective Wake Field and Hull Excitamentioning
confidence: 99%
See 1 more Smart Citation
“…The lower number of panels and high computational efficiency were experienced in the high-order panel methods. However, the effect of the singularity war [28,29] on numerical instability is still difficult to overcome in the high-order methods whereas the low-order panel method [2,9,11,28,30,31], i.e., the constant potential strength with an equal singularity density on a panel, is more stable to numerical computation for the analysis of a smooth hydrodynamic shape [25]. To improve the accuracy of high-or low-order panel method, the integrated trailing wake surface shall be an improved wake modelling [24,30,32].…”
Section: Introductionmentioning
confidence: 99%